2005
DOI: 10.1021/jm049798d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Automated Docking Programs as Virtual Screening Tools

Abstract: The performance of several commercially available docking programs is compared in the context of virtual screening. Five different protein targets are used, each with several known ligands. The simulated screening deck comprised 1000 molecules from a cleansed version of the MDL drug data report and 49 known ligands. For many of the known ligands, crystal structures of the relevant protein-ligand complexes were available. We attempted to run experiments with each docking method that were as similar as possible.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
219
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(228 citation statements)
references
References 66 publications
8
219
0
1
Order By: Relevance
“…Cummings et al [24] reported comparative performance of DockVision, Dock, GOLD, and Glide with respect to their ability to identify known ligands of HIV Protease (HVR), the human homolog of the mouse double minute 2 oncoprotein (HDM2), protein tyrosine phosphatase 1b (PTP1b), THR, and urokinase plasminogen activator (uPA). Of these, the ligands used for the first four were available from the authors.…”
Section: Jandj Screening Enrichment Setmentioning
confidence: 99%
See 2 more Smart Citations
“…Cummings et al [24] reported comparative performance of DockVision, Dock, GOLD, and Glide with respect to their ability to identify known ligands of HIV Protease (HVR), the human homolog of the mouse double minute 2 oncoprotein (HDM2), protein tyrosine phosphatase 1b (PTP1b), THR, and urokinase plasminogen activator (uPA). Of these, the ligands used for the first four were available from the authors.…”
Section: Jandj Screening Enrichment Setmentioning
confidence: 99%
“…A recent and valuable trend within the field has been the use of standard benchmarks on multiple methods [16][17][18][19][20][21][22]. For the work reported here, benchmarks were selected either for which previous versions of Surflex-Dock had been tested [16,17,19] in order to show the effects of new features, or where protein and ligand structures were publicly available along with performance of widely used methods [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent case study by Muthas et al indicated that post-filtering with pharmacophores was shown to increase enrichment rates in their investigated targets compared with docking alone [6] . Several studies have been performed to assess various DBVS methods and compare which docking programs are the most successful in identifying active hits [7][8][9][10] . The conclusion is that no docking program may outperform other docking programs for all the tested targets, and the performance of each tested docking program is highly dependent on the nature of the target binding site [5] .…”
mentioning
confidence: 99%
“…There are, fundamentally, two approaches to VS studies: i. structure-based virtual screening (SBVS), which requires knowledge of the 3D structures of target proteins to prioritize compounds by their complementarity to the binding site; and, ii. ligandbased virtual screening (LBVS), where no information on the protein is needed, instead, compounds known to bind to the protein are used as queries to search databases for new molecules possessing biological activity [21][22][23][24][25]. Fig.…”
Section: Virtual Screeningmentioning
confidence: 99%